الاتجاهات نحو اجراء الفحص و المشورة قبل الزواج لدى طلبة كلية التمريض في جامعة تشرين - عيسى, مروان (Latakia University Journal -Medical Sciences Series, 2018)
Pre-marital counseling is one of the health promotion activities which provided by maternity child health (MCH) programs. These services offered to young couples on their way to marriage to guide, educate and prepare them to form a healthy family. Pre-marital counseling is one of the most important strategies to prevent congenital malformations Genetic and many medical and psychosocial problems related to marriage. Genetic counseling, which is one of the most important components of premarital counseling, focuses on providing students with accurate knowledge and potential expectations and their percentage, leaving decision-making among the concerned and between the treating physician This study was conducted on a sample of 200 students from the Faculty of Nursing at Tishreen University. The purpose of this study was to evaluate the attitudes towards pre-marital examination and counseling among the students of the Faculty of Nursing at Tishreen University. . The results showed that the majority of respondents were positive attitudes towards pre-marital medical examination in most areas. The attitudes towards counseling and related laws were mostly positive. The study suggested that the importance of the role of nursing in providing genetic counseling and designing and implementing educational programs about The importance and benefits of premarital medical examination and advice تعد المشورة قبل الزواج من نشاطات تعزيز الصحة التي تقدمها برامج خدمات صحة الام و الطفل , هذه الخدمات تستهدف الفئات العمرية الشابة المقدمين على الزواج بهدف توجيههم و تثقيفهم و تحضيرهم لتكوين اسرة تتمتع بالصحة , و تعتبر المشورة قبل الزواج احد اهم الاستراتيجيات المتبعة للوقاية من التشوهات الخلقية الوراثية والعديد من المشاكل الطبية و النفسية الاجتماعية المتعلقة بالزواج . .تركز المشورة الوراثية و هي أحد اهم مكونات المشورة قبل الزواج على تزويد طالبيه بالمعرفة الدقيقة و التوقعات المحتملة و نسبتها تاركا اتخاذ القرار لذوي العلاقة فيما بينهم و بين الطبيب المعالج اجري هذا البحث على عينة قوامها 200 طالب و طالبة من كلية التمريض في جامعة تشرين و كان الهدف من هذه الدراسة تقييم الاتجاهات نحو اجراء الفحص و المشورة قبل الزواج لدى طلبة كلية التمريض في جامعة تشرين. وقد أظهرت النتائج أن غالبية أفراد العينة كانت اتجاهاتهم نحو الفحص الطبي قبل الزواج ايجابية في معظم المحاور.كما كانت الاتجاهات نحو المشورة و القوانين المتعلقة بها ايجابية في معظمها لذلك اقترحت الدراسة تعزيز أهمية دور التمريض في تقديم المشورة الوراثية و تصميم و تنفيذ برامج تثقيفية حول أهمية و فوائد الفحص الطبي قبل الزواج و اعطاء المشورة المتعلقة بذلك